A comparative study of sports achievement motivation among national level athletes - Dhull, S. (International Journal of Physical Education and Sports, 2017)
The purpose of the present study was to determine the differences and level of Achievement motivation in national basketball, national hockey and national Badminton players. The age of the subjects was between 19-24 years. The total number of players who participated in present Investigation was 63 (21 Badminton, 21 Basketball and 21 hockey players). One Way analysis of variance and Least Significant Difference Post-hoc test was used to analyse the Data, the level of significance for the study was chosen as 0.05. The results of the study revealed that National basketball players had higher and Badminton players had a lower level of Achievement motivation amongst the group. Further as per the norms of the Questionnaire National Basketball and National Hockey players had high level of achievement motivation and National Badminton players had moderate level of achievement motivation.